DAMPAK KEBIJAKAN PENGEMBANGAN USAHA MASYARAKAT MIKRO DI KELURAHAN MADIDIR WERU KECAMATAN MADIDIR KOTA BITUNG - DEWI, HENDRIKA PUTRI MARSITA; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2020)
This study aims to determine the impact of micro-community business development policies in Madidir WeruVillage, Madidir District, Bitung City. This type of research used in this study is qualitative research. Thetheory used is based on five dimensions, namely: the impact of policy on public problems and the impact ofpolicy on the people involved, the impact of the policy on circumstances and groups outside the goals orobjectives of the policy, the impact of the policy on the present and the future, the direct costs incurred andindirect costs borne by the community. Data sources used are primary data and secondary data. Datacollection techniques used were observation, interviews and documentation, data obtained from varioussources were obtained and then analyzed into a conclusion. The results of this study that the impact ofpolicies on micro-business development based on capital, marketing, human resource capabilities andtechnological limitations in terms of the impact of policies on public problems and the impact of policies onpeople involved, the impact of policies on circumstances and groups outside the target or policy objectives,the impact of the policy on the present and future conditions, the direct costs incurred and the indirect costsborne by the community shown in the program in the form of venture capital have a successful and successfulimpact on the development of microbusiness communities. However, there is a need for community initiativesto find information about existing programs and are being carried out by the government to developbusinesses.Keywords: Policy Impact, Business Development, Micro Society.